How best (not) to address the Ukraine crisis - Glauber, Joseph W.; Smith, Vincent H. (American Enterprise Institute, 2022)
Russia’s invasion of Ukraine has disrupted global wheat, corn, and other markets. Given relatively low global stocks for major staple foodstuffs, many analysts predict that food insecurity will increase among poor households in low-income countries. Understandably, many world leaders, including the Biden administration, are concerned about how to best address a potential global hunger crisis. However, in the rush to “do something,” leaders need to consider the most efficient policies to address the crisis and avoid ill-considered policies that may do little to address the actual problems and could result in unintended consequences that may linger well past the crisis itself.